2002
DOI: 10.1034/j.1399-6576.2002.461006.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among anesthesiologists in Denmark, 1973–95

Abstract: In Denmark there is no evidence of a high mortality risk in consultant anesthesiologists compared with other consultants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
(18 reference statements)
0
13
1
Order By: Relevance
“…In contrast to the Swedish results, no increased risks were found in the Danish, Norwegian, or Finnish studies (2)(3)(4). Both the Norwegian and Finnish studies were, however, rather small and also hampered by methodological weaknesses (3, 4).…”
Section: Is the Life Expectancy Of Anesthesiologists Decreased?contrasting
confidence: 43%
See 1 more Smart Citation
“…In contrast to the Swedish results, no increased risks were found in the Danish, Norwegian, or Finnish studies (2)(3)(4). Both the Norwegian and Finnish studies were, however, rather small and also hampered by methodological weaknesses (3, 4).…”
Section: Is the Life Expectancy Of Anesthesiologists Decreased?contrasting
confidence: 43%
“…Unfortunately, the results of the Swedish study were not published until very recently (1). In the same issue of Acta Anaesthesiologica Scandinavica, similar studies from Denmark, Finland, and Norway also appeared (2)(3)(4).…”
Section: Is the Life Expectancy Of Anesthesiologists Decreased?mentioning
confidence: 91%
“…Long‐standing stress at work can adversely affect physical and mental health, and is associated with, e.g., muscular strains and injuries, 8 cardiovascular diseases 8–11 and drug or alcohol abuse culminating in suicide 12,13 . Although causality is not yet found, higher mortality rates 14 and suicidality or suicide rates among anaesthesiologists 12,13,15 were reported in several studies, whereas others found equal mortality rates 16–18 …”
mentioning
confidence: 99%
“…1 Due to its methodological flaws, the study was heavily criticized but it prompted a survey in each of the Nordic countries. [2][3][4][5] In our previous report 2 , we investigated mortality rates and demonstrated that anaesthesiologists in Finland had a lower age-standardized mortality rate than other specialists, which was due to the different age structures of the two groups. Our previous survey included only 18 deceased anaesthesiologist.…”
Section: Editorial Commentmentioning
confidence: 97%